Cecil: A moment or a movement? Analysis of media coverage of the death of a lion, Panthera leo - Macdonald, D; Jacobsen, K; Burnham, D; Johnson, P; Loveridge, A; Johnson, P (MDPI, 2016)
The killing of a satellite-tagged male lion by a trophy hunter in Zimbabwe in July 2015 provoked an unprecedented media reaction. We analyse the global media response to the trophy hunting of the lion, nicknamed “Cecil”, a study animal in a long-term project run by Oxford University’s Wildlife Conservation Research Unit (WildCRU). We collaborated with a media-monitoring company to investigate the development of the media coverage spatially and temporally. Relevant articles were identified using a Boolean search for the terms Cecil AND lion in 127 languages. Stories about Cecil the Lion in the editorial media increased from approximately 15 per day to nearly 12,000 at its peak, and mentions of Cecil the Lion in social media reached 87,533 at its peak. We found that, while there were clear regional differences in the level of media saturation of the Cecil story, the patterns of the development of the coverage of this story were remarkably similar across the globe, and that there was no evidence of a lag between the social media and the editorial media. Further, all the main social media platforms appeared to react in synchrony. This story appears to have spread synchronously across media channels and geographically across the globe over the span of about two days. For lion conservation in particular, and perhaps for wildlife conservation more generally, we speculate that the atmosphere may have been changed significantly. We consider the possible reasons why this incident provoked a reaction unprecedented in the conservation sector.